Identification of the hot spot residues for pyridine derivative inhibitor CCT251455 and ATP substrate binding on monopolar spindle 1 (MPS1) kinase by molecular dynamic simulation. Issue 3 (11th February 2019) - Chen, Kai; Duan, Wenxiu; Han, Qianqian; Sun, Xuan; Li, Wenqian; Hu, Shuangyun; Wan, Jiajia; Wu, Jiang; Ge, Yushu; Liu, Dan
Abstract : Protein kinase monopolar spindle 1 plays an important role in spindle assembly checkpoint at the onset of mitosis. Over expression of MPS1 correlated with a wide range of human tumors makes it an attractive target for finding an effective and specific inhibitor. In this work, we performed molecular dynamics simulations of protein MPS1 itself as well as protein bound systems with the inhibitor and natural substrate based on crystal structures. The reported orally bioavailable 1 h-pyrrolo [3, 2-c] pyridine inhibitors of MPS1 maintained stable binding in the catalytic site, while natural substrate ATP could not stay. Comparative study of stability and flexibility of three systems reveals position shifting of β-sheet region within the catalytic site, which indicates inhibition mechanism was through stabilizing the β-sheet region. Binding free energies calculated with MM-GB/PBSA method shows different binding affinity for inhibitor and ATP. Finally, interactions between protein and inhibitor during molecular dynamic simulations were measured and counted. Residue Gly605 and Leu654 were suggested as important hot spots for stable binding of inhibitor by molecular dynamic simulation. Our results reveal an important position shifting within catalytic site for non-inhibited proteins. Together with hot spots found by molecular dynamic simulation, the results provide important information of inhibition mechanism and will be referenced for designing novel inhibitors.